2008
DOI: 10.5016/1806-8774.2008.v10p6
|View full text |Cite
|
Sign up to set email alerts
|

<b>Pharmacological Effects of <i>Allium Sativum</i> L. (Garlic)</b>

Abstract: Garlic (Allium sativum L.) is a bulbous herb used as a food item, spice and medicine in different parts of the world. Its medicinal use is based on traditional experience passed from generation to generation. Researchers from various disciplines are now directing their efforts towards discovering the effects of garlic on human health. Interest in garlic among researchers, particularly those in medical profession, has stemmed from the search for a drug that has a broad-spectrum therapeutic effect with minimal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 171 publications
1
55
0
2
Order By: Relevance
“…Las anormalidades lipídicas incluyen altos niveles de LDL (colesterol de lipoproteínas de baja densidad), triglicéridos elevados y HDL bajo (lipoproteínas de colesterol de alta densidad). El colesterol presente en la β-lipoproteína (LDL) y pre-B-lipoproteína se deposita en los vasos sanguíneos, mientras que α-lipoproteína (HDL) ayuda a reducir el colesterol sérico (2,3) .…”
Section: Introductionunclassified
“…Las anormalidades lipídicas incluyen altos niveles de LDL (colesterol de lipoproteínas de baja densidad), triglicéridos elevados y HDL bajo (lipoproteínas de colesterol de alta densidad). El colesterol presente en la β-lipoproteína (LDL) y pre-B-lipoproteína se deposita en los vasos sanguíneos, mientras que α-lipoproteína (HDL) ayuda a reducir el colesterol sérico (2,3) .…”
Section: Introductionunclassified
“…Phytochemical screening of Allium sativum revealed it is a rich source of important organics compound, which include steroids, saponins and flavonoids such as quercetin and kaempherol. They also are characterized by a high content of organosulphur compounds including allicin, ajoene, cephaene, zwiebalanes and zpropanthiol-s-oxide which are responsible for the lachrymatory pungency, typical smell and taste (Singh and Singh, 2008). More so, chronic and unregulated intake of Allium sativum was reported to cause impairment of normal red cell membrane stability in addition to an increased susceptibility to oxidative stress and formation of Heinzbody anemia.…”
Section: Introductionmentioning
confidence: 99%
“…More so, chronic and unregulated intake of Allium sativum was reported to cause impairment of normal red cell membrane stability in addition to an increased susceptibility to oxidative stress and formation of Heinzbody anemia. Acute toxicity studies in rodents also reveal LD 50 of Allium sativum to be 3g/Kg body weight (Singh and Singh, 2008) Sickle cell anemia is an inherited blood disease, in which, when red cells are deoxygenated, produce a fibrous polymer which stiffen erythrocyte membrane and alters ionic transport. In addition it has generally been observed that human erythrocytes are perhaps the cells most exposed to peroxidative damage by free radicals due to the high cellular concentration of oxygen and hemoglobin; a potentially powerful promoter of oxidative processes (Rother et al, 2005; Jaiswal and Rizvi, 2011) However other studies shown that the red blood cell protects itself against oxidative damage by antioxidants located in both cytosolic and membrane domains which counter the effect of antioxidant and also free radicals (Rai et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The active constituents are sulfur-containing compounds that are rapidly absorbed and metabolized. Numerous studies on garlic have suggested that garlic lowers total cholesterol concentrations favorably altering HDL/LDL ratios (Singh andSingh, 2008, Bordia (1981). Garlic contains at least 33 sulfur compounds, several enzymes and the minerals vitamins, fiber amino acids and water (Josling, 2005;Fenwick and Hanley, 1985).…”
Section: Issn: 2320-5407mentioning
confidence: 99%